Pesticide Toxicity Profile: Wood Treatment Pesticides - Frederick M. Fishel (EDIS)
This document provides a general overview of human toxicity and a cross reference of chemical, common and trade names of common wood treatment pesticides registered for use in Florida. This guide summarizes some of the more commonly-used wood preservatives. This document is PI-92, one of a series of the Pesticide Information Office, Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date December 2005.